Perception of Philippine Army personnel of 3rd infantry (Spearhead) Division, Camp General Macario Peralta, Jr., Jamindan Capiz on military women joining combat - Dolloso, Rhoselyn T.; Provido, Angeli Paullette D. (2005.)
For the past years , there have been several studies conducted about the military. Most of these studies centered on the historical, organizational and institutional structure of the military. Only a few of these are empirical studies on the military's social aspect. This is an exploratory study on the Perception of Philippine Army Personnel of 3rd Infantry (spearhed) division in Camp Gen. Macario Peralta Jr., Jamindan, Capiz towards having military women in front line combat. Using a 5-point Likert scale survey questionnaires, the researchers were able to conduct the study on 88 military men coming from the different units in the camp. Aside from survey, the researchers also utilized key-informant interviews and focused group discussions (FGD) in gathering primary data. This study particularly addressed the following objectives: (1) to know what are the bases of task(s) or function(s) usually given/assigned to military women; (2) determine the views of military men in women in the military (3) to determine what is the perception of military men on women joining front-line combat; and (4) to know what factors influence these perceptions., The study results showed that the primary bases of assigning tasks or functions for military women are their educational background and specialization upon their entry into the service. Upon training, military women are made to choose their area of specialization and then they are assigned to their chosen offices. The researchers found out that men's perception towards women joining combat is undecided. Military men acknowledge the presence and the essence of women in the military. They have high regard on them as superiors (officers) and comrades, but they want to maintain the status of having military women confined in office duties and jobs where no excessive physical strength is needed. The researchers also found out that women's is also undecided about them joining combat . There is a possibility of sending military women to the front-lines, but perhaps for a couple more years.
Thesis (Undergraduate, Bachelor of Arts in Political Science-Management) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo. 2005.
Keywords: Women in the military -- Philippines